ancang Bangun Sistem Kontrol Pada Mesin Pelarut PCB (Printed Circuit Board) - dwyjuliano, wawwa; Mardianto, Eko (entries, 2024)
Printed Circuit Board (PCB) dissolving is the process of removing copper layers on PCBs to produce conductive path patterns. On a hobby scale, this process is often done manually, takes a long time and involves repetitive physical work. By designing a control system on a PCB solvent machine, the dissolving process can be more efficient. The automated system will automate most of the steps in the dissolving process, reducing the time it takes and improving operational efficiency. The automated control system will provide a more accurate and consistent solution result compared to manual processes, reducing human error and improving product quality. The impact of PCB dimensions on the dissolving process can also be minimized by automatic adjustment, ensuring uniform and optimal outcomes on various PCB sizes.Keywords : PCB dissolving, Control